2011
DOI: 10.1007/s10822-011-9433-1
|View full text |Cite
|
Sign up to set email alerts
|

Docking glycosaminoglycans to proteins: analysis of solvent inclusion

Abstract: Glycosaminoglycans (GAGs) are anionic polysaccharides, which participate in key processes in the extracellular matrix by interactions with protein targets. Due to their charged nature, accurate consideration of electrostatic and water-mediated interactions is indispensable for understanding GAGs binding properties. However, solvent is often overlooked in molecular recognition studies. Here we analyze the abundance of solvent in GAG-protein interfaces and investigate the challenges of adding explicit solvent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 47 publications
2
74
0
Order By: Relevance
“…The charge of the ring oxygen of L-fucose is −0.68. Thus L-fucose can interact electrostatically with the positively charged side chain of Lys 5 and in this way contributing to its strongest binding affinity (Samsonov et al 2011) The docking of L-fucose to 2 and 3 showed similar docking poses, however slightly more different but in a similar region to the pose of L-fucose to 1 (Online Resource Fig. 14 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The charge of the ring oxygen of L-fucose is −0.68. Thus L-fucose can interact electrostatically with the positively charged side chain of Lys 5 and in this way contributing to its strongest binding affinity (Samsonov et al 2011) The docking of L-fucose to 2 and 3 showed similar docking poses, however slightly more different but in a similar region to the pose of L-fucose to 1 (Online Resource Fig. 14 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Where the main interest lies in identifying a heparin binding site, the calculations need not provide a full simulation of the protein-ligand complex in solution and cannot be relied on for the exact orientation of the ligand at the binding site (Forster and Mulloy, 2006). However, where detailed analysis of the interaction is required, greater care must be taken to accommodate complexities such as the conformational plasticity of the iduronate residue and the role of solvent in the interaction (Samsonov et al, 2011). A strategy for high-throughput screening of heparin/HS sequences has also been developed using docking calculations (Raghuraman et al, 2006).…”
Section: Pharmacology Of Heparin and Related Drugsmentioning
confidence: 99%
“…Nevertheless, the relative lack of experimental structural data for these systems, combined with a growing awareness of their biological significance, has led to a number of innovative approaches to GAG docking. Recent examples include advances in the prediction of GAG binding sites [38,39], improvement in pose prediction via inclusion of specific bound waters [40], co-complex generation via threading and superimposition [41], mimetic discovery [42], as well as combining spectroscopic data with GAG modelling [43,44]. Very recently, an online utility for the automatic generation of 3D structures for GAGs has appeared (www.glycam.org/gag, [25]) that should find application in GAG modelling.…”
Section: Recent Advances In Computational Carbohydrate Dockingmentioning
confidence: 99%